Circulating miRNAs as Putative Biomarkers of Exercise Adaptation in Endurance Horses - Cappelli, Katia; Capomaccio, Stefano; Viglino, Andrea; Silvestrelli, Maurizio; Beccati, Francesca; Moscati, Livia; Chiaradia, Elisabetta (Frontiers in Physiology, 2018)
Endurance exercise induces metabolic adaptations and has recently been reported associated with the modulation of a particular class of small noncoding RNAs, microRNAs, that act as post-transcriptional regulators of gene expression. Released into body fluids, they termed circulating miRNAs, and they have been recognized as more effective and accurate biomarkers than classical serum markers. This study examined serum profile of miRNAs through massive parallel sequencing in response to prolonged endurance exercise in samples obtained from four competitive Arabian horses before and two hours after the end of competition. MicroRNA identification, differential gene expression analysis and a protein-protein interaction network showing significantly enriched pathways of target gene clusters, were assessed and explored. Our results show modulation of more than 100 miRNAs probably arising from tissues involved in exercise responses and indicating the modulation of correlated processes as muscle remodelling, immune and inflammatory responses. Circulating miRNA high-throughput sequencing is a promising approach for sports medicine for the discovery of putative biomarkers for predicting risks related to prolonged activity and monitoring metabolic adaptations.